Increased RISK for 47, XXY on cell‐free DNA screen: Not always Klinefelter syndrome. (19th January 2021) - Ronzoni, Luisa; Bedeschi, Maria Francesca; Silibello, Gaia; Accurti, Veronica; Di Segni, Marina; Nicotra, Valeria; Vizziello, Paola; Lalatta, Faustina
Key Points: What's already known about this topic? Noninvasive cell‐free DNA (cfDNA) tests allow prenatal identification of high risk for Klinefelter syndrome cfDNA test requires a prenatal or postnatal confirmation to reach a definitive diagnosis What does this study add? In a significant number of cfDNA tests, results reporting increased risk for 47, XXY were not confirmed on diagnostic testing Invasive procedures must always be discussed to exclude chromosomal variations with a more severe phenotype